Biological properties and phytochemical characterization from Miconia chamissois Naudin aqueous extract - Gomes, Lorena Ferreira (2021)
The objective of this study was to evaluate biological and phytochemical properties of the aqueous extract from the leaves of Miconia chamissoisNaudin (AEMC). Phytochemical properties were assessed by analyzing the chromatographic profile and the polyphenol content of AEMC. Biological properties evaluation wasconducted based on cytotoxicity assay and by evaluating the antioxidant, antimicrobial, and enzymatic inhibition activities. Results indicated the presence of phytochemicals in AEMC such as flavonoids and polyphenols, including rutin, isoquercitrin and vitexin derivatives. AEMC showed antioxidant activity, which may be attributed to the high polyphenolic content. Moreover, AEMC demonstrated in vitro enzyme inhibition activity against tyrosinase and alpha-amylase, as well as showed low cytotoxicity. On the other hand, AEMC exhibited weak antimicrobial activity against S. aureusand C. albicans. Thus, AEMC is a promising alternative in search of potential drugs for the treatment of diseases induced by oxidative stress and inflammation, conditions due to hyperpigmentation processes, such as melisma, as well as for diabetes.